Visual Teaching Tools: Concept Maps - Lauren Dillard; Brian E. Myers (EDIS)
AEC-390, a 4-page illustrated fact sheet by Lauren Dillard and Brian E. Myers, describes these educational tools, what they are, types of concept maps, and their purpose. Published by the UF Department of Agricultural Education and Communication, May 2008.